Síntese, caracterização e atividade antimicrobiana de compostos heterocíclicos da classe 2,3-diidro-1,3,4-oxadiazol derivados de N-acilhidrazonas - Oliveira, Cledualdo Soares de (2013)
Among the heterocyclic compounds, 1,3,4-oxadiazole represents an important unit for the development of new drugs, since compounds containing this unit present a broad spectrum of biological activities such as antibacterial, antifungal, analgesic, anti- inflammatory, antiviral, antitumor, antihypertensive, anticonvulsant, etc. We describe the synthesis, characterization and antimicrobial activity of heterocyclic compounds of class 2,3-dihydro- 1,3,4-oxadiazole, specifically, 3-acetyl-2,5-diaryl-2,3-dihydro-1,3,4-oxadiazole, that were obtained as racemic mixture from the reaction of cyclization of N-acylhydrazones using acetic anhydride. Compounds were divided into three sets congeners as follows: series 1 (2-aryl-3- acetyl-5-(pyridin-4-yl)-2,3-dihydro-1,3,4-oxadiazol), series 2 (2-(5-nitrofuran-2-yl)-3-acetyl- 5-aryl-2,3-dihydro-1,3,4-oxadiazol) and series 3 (2-(4-acetoxyphenyl)-3-acetyl-5- aryl-2,3- dihydro-1,3,4-oxadiazol). All compounds were characterized by spectroscopic techniques IR, 1H-NMR, 13C-NMR and mass spectrometry. In the evaluation of the in vitro antimicrobial activity, compounds of the series 2 exhibit efficient activity against several strains of Staphylococcus aureus with minimum inhibitory concentration in the range of 8 to 32μg/mL, being more potent than the standard drug chloramphenicol, and good antifungal activity against six Candida strains with minimum inhibitory concentration values ranging from 64 to 512 μg/mL.